Sinergisme Fraksi Butanol Metabolit Sekunder Kapang Endofit 1.3.11 dengan Doxorubicin dalam Modulasi Daur Sel T47D dan MCF-7 - SHIRLY KUMALA; EDY MEIYANTO; MUTHI IKAWATI; RIRIS ISTIGHFARI JENIE (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
The synergic effects of n-butanolic fraction of secondary metabolite of endophytic fungus 1.3.11 (FB) and doxorubicin (Dox) on cell cycle regulation and the expression of Bcl-2 gene expression were investigated on MCF-7 and T47-D cells by iiow cytometry and immunocytochemical techniques respectively. The results showed that after 12 hours of incubation period with FB at its IC50 dose, MCF-7 cell cycle was inhibited at G1 phase while Dox inhibited the cell cycle at G2/M phase. Similar results were observed in T47-D cells when incubated with Dox and FB individually under the same treatment condition. Further treatment was then performed to these cells where both Dox and FB were combined at their IC50 and lC50 dose and added to incubate with the cells over 12 hours period. Interestingly, the modified treatment combination showed that MCF-7 and T47-D cell cycle regulation were inhibited at G2/M phase. Our immunocytochemical study also showed no significant inhibition suppression of Bel-2 gene expression in both MCF-7 and T47-D cells when compared with their corresponding positive control after treatment with FB and Dox or both combined FB and Dox at 1C50 and IC50 dosage over 15 hours incubation.